Perbandingan Metode Naïve Bayes dan C4.5 Klasifikasi Status Gizi Bayi Balita - Alter Lasarudin; Hilmansyah Gani; Misran Tomayahu (SPECTA Journal of Technology, 2022)
In supporting good services, an orderly, neat and meticulous work procedure are needed. So that information will be produced quickly, precisely and accurately. In health institution, there is a lot of data which increase every year. One of them is data on toddler growth and development. However, the excessive data have consequences more difficult to learn the data were only used as archives. The use of data mining techniques is expected to help in overcoming the imperfent development of toddlers. In this study, researcher compared the classification techniques of performance methods (C4.5) and Naïve Bayes. The attributes used in this research consist of Gender, Age, Weight, Body Length, Region and Growth with 500 data. The results of the research conducted, based on the accuracy and recall values ​​of Naive Bayes were higher than the accuracy value of C4.5 with an accuracy value 94.20% for Naive Bayes, and C4.5 with an accuracy value of 85.80%. Although, in this study the Precision level is higher Naïve Bayes which is 94.20% compared to C4.5 which is 85.80%. The final result of this research is that the Naïve Bayes method is better used than the decision tree method. Keywords: Data Mining, Classification, Naïve Bayes, C4.5